Synthesis, Spectroscopic and Thermal Characterization of a New Sustainable Polymer - Çankaya, Nevin; Turan, Nevin (My University, 2021)
Copolymerization is a very important method in the synthesis of products having the physical and chemical properties sought in industrial sense. In this paper, the copolymerization of N-(4-nitrophenyl) acrylamide monomer with D-limonene was carried out and LIM-co-NPA copolymer was synthesized by free radical chain polymerization reaction. The structure of sustainable copolymer of limonene was chemically characterized by FT-IR, 1H-NMR spectroscopic techniques. In addition, thermal stability of copolymer investigated by TGA/DTG/DTA simultaneous thermal analysis methods. The spectroscopic results are compatible with the amide or limonene polymers synthesized in the literature. From the important thermal results of the sustainable copolymer, it has been found that the initial decomposition temperature is 226°C, and the maximum decomposition temperatures is 329°C, glass transition temperature at 261°C and crystallization temperature at 340°C. It can be said that this promising sustainable copolymer is suitable for other mechanical, physical and biological study and research fields.
Keywords: D-limonene; Synthesis and Characterization; Copolymer; Thermal Stability; Sustainable Polymer